In the wake of a major hurricane: Differential effects on early vs. late successional seagrass species. Issue 5 (27th August 2019) - Congdon, Victoria M.; Bonsell, Christina; Cuddy, Meaghan R.; Dunton, Kenneth H.
Abstract: At least 18 major storms have struck the Gulf of Mexico and Caribbean in the past 50 yr including Hurricane Harvey, a Category 4 storm that passed over extensive seagrass beds in the western Gulf of Mexico and became the second‐most expensive U.S. hurricane. We sought to identify the effects of an extreme hurricane on sediment physicochemical characteristics and seagrass species with contrasting life histories and morphologies. Surprisingly, Harvey's intense wind speeds resulted in decreases in blade length, vegetative cover, and greater overall loss of Thalassia, a persistent climax species relative to Halodule, a prolific pioneer species. Sediment ammonium and grain size changed, but not organic carbon. Our results indicate that effects of wind intensity are not only restricted to the differential impacts on seagrasses, but on the physicochemical characteristics of the sediments. These changes, coupled with the slow colonization abilities of Thalassia, may prolong recovery of disturbed seagrass meadows.